Staphylococcal canine pyoderma: species identification and drug sensitivity (Revista de Ciências Agroveterinárias, 2006)
This paper reports the results of bacteriological examination on clinical cases of pyoderma in dogs, patients from the Veterinary Hospital, ULBRA University, during the year of 2005. The disease was diagnosed in different degrees of evolution. Isolated of Staphylococcus sp. from 42 samples were taken. Samples were examined regarding phenotypic characteristics, based on colony pigmentation, kind of hemolysis, growth and reaction in Baird-Parker (BP) medium, DNAse production, slide coagulase test (Clumping Factor), sugar fermentation, salt tolerance, MR, VP and Polimixin B behavior. The antimicrobial susceptibility tests were performed by the disk diffusion method (Kirby-Bauer). The most prevalent staphylococal species identified was Staphylococcus intermedius, regardless of the extension of the disease in the examined patient. The antimicrobial susceptibility tests showed at least 70% of sensitivity or more to amoxicilin+clavulanic acid, ceftiofur, cefalexyn, amicacyn and enrofloxacyn.
Keywords: Canine pyoderma; Staphylococcus intermedius; antibiotics; susceptibility.